ANALYSIS OF COMMUNITY PARTICIPATION IN THE DEVELOPMENT OF WONOREJO TOURIST VILLAGE IN JATIYOSO, KARANGANYAR REGENCY - Sifaul Arief; Chatarina Muryani; Inna Prihartini (GeoEco, 2019)
The research is intended to find (1) the spread of tourist resort in Wonorejo Village, Jatiyoso, Karanganyar (2) the potential of tourist resort owned by Wonorejo Village, Jatiyoso, Karanganyar (3) community participation in tourist development Wonorejo Village, Jatiyoso, Karanganyar (4) characteristics of community based tourism in Wonorejo Village, Jatiyoso, Karangayar (5) the right development direction of Wonorejo tourism Village, Jatiyoso, Karanganyar (6) implementation of Geography Class XI High School learning.Type of this research descriptive qualitative. The population of this research is all of tourist resort and community in Wonorejo Village. Sampling was done in two methods which were purposive sampling and accidental sampling. Data collecting techniques are field observation, indepth interview, and documentations. Data analysis is using interactive models (Miles-Huberman) and to comparison potential of tourist resort using analysis A4, to comparison community partitipation using partitipation scale of Arnstein, characteristics of community based tourism, and SWOT.The result of the research are, (1) The distribution of tourist resort in the Wonorejo of Village in the central part of the village. (2) potential tourism objects in Wonorejo Village are found in potential classes. (3) high level of community participation is the level of delegated power and citizen control. (4) community based tourism (CBT)  in Wonorejo Village runs well, seen from the high participation of community, equitable distribution of benefits, having a driving figure, good relations with the local government, and maintaining tourism by promoting cultural values (local wisdom) and environment. (5) direction for the development of tourism villages by improving the quality of human resources, tourist resort and local wisdom. (6) the implementation of Geography learning through the making of teaching materials.